Science, Education, and Equality, in the United States - Barritt, L.S. (Pedagogische Studiën, 1975)
What are the effects of school experiences on children? Is it possible for schools as instruments of asociety to correct past injustices, done for example,the poor or to members of a minority race?These are the questions that have guided a great•i^al of research during the last ten years in theUnited States. It is the purpose of this paper to^ßview a portion of the evidence and some reactionsfo it before making general comments about these'ssues as researchablè questions.